Applications of advanced oxidation processes: present and future - Suty, H.; De Traversay, C.; Cost, M. (Water science and technology, 2004)
The use of advanced oxidation processes (AOPs) to remove pollutants in various water treatment applications has been the subject of study for around 30 years. Most of the available processes (Fenton reagent, O3 under basic conditions, O3/H2O2, O3/UV, O3/solid catalyst, H2O2/Mn+, H2O2/UV, photo-assisted Fenton, H2O2/solid catalyst, H2O2/NaClO, TiO2/UV etc.) have been investigated in depth and a considerable body of knowledge has been built up about the reactivity of many pollutants. Various industrial applications have been developed, including ones for ground remediation (TCE, PCE), the removal of pesticides from drinking water, the removal of formaldehyde and phenol from industrial waste water and a reduction in COD from industrial waste water. The development of such AOP applications has been stimulated by increasingly stringent regulations, the pollution of water resources through agricultural and industrial activities and the requirement that industry meet effluent discharge standards. Nevertheless, it is difficult to obtain an accurate picture of the use of AOPs and its exact position in the range of water treatment processes has not been determined to date. The purpose of this overview is to discuss those processes and provide an indication of future trends.